Obtenção de compostos de inclusão Cilostazol-β-Ciclodextrina visando à melhoria da solubilidade - Salvini, Diohãne Vanessa (2018)
Cyclodextrins are considered to be a new class of pharmaceutical excipients. The most common pharmaceutical application of cyclodextrins are used to improve the aqueous solubility of drugs and to improve bioavailability after, for example, oral administration. They are called α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, consisting of cyclic oligosaccharides. Cilostazol is a vasorelaxing drug and acts as an inhibitor of platelet aggregation. Displays low aqueous solubility, variable bioavailability. Thus, the main objective of the study was to investigate the possibility of improving the solubility of Cilostazol via β-CD complexation. Phase solubility studies revealed the existence of a 1: 1 complex between cilostazol and β-CD. Inclusion complexes prepared were characterized by UV-vis, exhibiting positive changes in solubility.